Pendampingan Penerapan Keterampilan Menulis melalui Strategi Image Streaming pada Pembelajaran Bahasa Siswa Kelas VII SMPN 1 Sanrobone - Ihramsari Akidah; Rizkariani Sulaiman; Andi Puspitasari (Jurnal Pengabdian Masyarakat Indonesia Sejahtera, 2023)
Looking at the nature of the Image Streaming strategy, it is hoped that the Image Streaming strategy can be used as an effective and appropriate strategy when used in learning to write narratives in the form of short story texts. This service aims to provide continuous and continuous learning so that it is not just a matter of putting together a complete word but can be put into writing using the right strategy; improving students' skills by implementing appropriate learning strategies, namely the image streaming strategy in the learning process so that students can practice expressing their ideas in written form; find out the extent to which students' abilities have increased in writing skills to compose a complete sentence through the Image streaming strategy. In order to achieve this goal, the service team carried out planning by chronologically chronologically lining up its implementation starting from discussions, providing materials, providing assistance and implementing the Image Streaming strategy, as well as evaluating the results of student activities. Therefore, the final result of this community service is that it can provide motivation and useful information for students to be more active in the teaching and learning process in class.